ENHANCING EMPLOYABILITY SKILLS THROUGH THE DEVELOPMENT OF AN INDUSTRIAL CLASS MODEL: EVIDENCE FROM INDONESIAN VOCATIONAL HIGH SCHOOLS - Patta, Andi Umar; Gani, Hamsu Abdul; Purnamawati, Purnamawati (Pascasarjana Universitas Negeri Makassar, 2026)
This study aims to develop and validate an Industrial Class Model designed to enhance employability skills among vocational high school students in Indonesia. Despite longstanding reforms in vocational education, graduates continue to face challenges in meeting labor market expectations, primarily due to weak industry engagement and limited focus on transferable soft skills. Using a quantitative research design grounded in Modified Model (ADDIE, Dick & Carey, 4D (Define, Design, Develop, Disseminate), Borg & Gall, and Prototyping), this study combines quantitative surveys field observations to assess current practices and test the effectiveness of the Industrial Class Model. The model integrates co-designed instruction, co-teaching with industry practitioners, and experiential learning through real-world projects. Data were collected from students, vocational teachers, and industry professionals across vocational schools in Makassar. The findings show that the model significantly improves students’ attitudes, instructional engagement, experiential learning, and, most importantly, core employability competencies such as communication, teamwork, discipline, and problem-solving. Mean scores across key variables ranged from 7.4 to 8.5 on a 10-point scale, with the highest scores in student attitude (8.5) and social relatedness (8.3). However, the study also identifies areas for further development, particularly in fostering student autonomy and intrinsic motivation. The results affirm the importance of industry-integrated pedagogy and provide evidence for a scalable, replicable instructional framework that aligns vocational education with workforce demands. The Industrial Class Model offers a practical solution for improving graduate readiness and can serve as a blueprint for vocational education reform in Indonesia and similar contexts globally.